"Victims of empire: WWI ex-servicemen and the colonial economy of wartime sacrifices in postwar British Nigeria". Issue 1 (2nd January 2019) - Njung, George N.
ABSTRACT: The First World War (1914–18) saw the recruitment of over 20, 000 Nigerian soldiers to defend the British African empire. When the war ended, the chaotic demobilization process transformed the surviving soldiers into ex-servicemen. This article examines the problems that faced the ex-servicemen in the postwar economy of British Nigeria by focusing on the categories of demobilization and resettlement, employment, finances, war wages, gratuities and pensions, and health care. It emphasizes that the neglect of the men by the colonial government in those categories meant that the men had sacrificed for the British empire far more than the empire ever remitted. The article uses the situation of the men to problematize the political economy of a compartmentalized colonial state that enforced a duality of status – citizens vs colonial subjects – for Europeans and Africans. Based on data collected from the Nigerian and British national archives, the study reveals how Nigerian WWI ex-servicemen fell victim to the logic of British colonialism which, like all others, prioritized profit above all else. Consequently, after having served the colonial state, the men became undermined within their respective African communities without a simultaneous elevation of their status within the colonial state.